STANDARD OF FULFILMENT OF REQUIREMENTS IN THE APPLICATION OF TQM IN SLOVAK REPUBLIC - Iveta Paulova (Vallis Aurea, 2017)
In practise are TQM approaches applied through the EFQM Excellence Model and therefore research is focused on organizations which are applying this model and their level of performance in individual criteria are rated within the National Quality Award of the Slovak Republic. The paper objective is describe the current state of implementation of human resources management in organizations that participated in National Quality Award of the Slovak Republic. Organizations included in the research have achieved the highest rating and also are applying the EFQM Excellence Model. The model is composed of several areas. In the area of human resources management are important the approaches of implementation of human resources management and subsequent prove of results if the stated strategy is carried out efficiently to the employee satisfaction. This article is written within the project VEGA: "The readiness of industrial enterprises to implement the requirements of standards for quality management systems ISO 9001:2015 and environmental management systems ISO 14001:2014”